Media Belajar Digital Berbasis Kearifan Lokal Sebagai Sumber Bacaan Dongeng Sastra Anak - Nur Fajrie; Vina Aryani; Lintang Kironoratri (Elementary Teacher Education Program, Majalengka University, 2024)
The purpose of this research is to analyze the media needs of children's literature fairy tales in grade III at SD N 1 Tuko, Grobogan Regency. This research used mixed methods with a sequential exploratory model. The research subjects were the third grade teacher and five third grade students with purposive sampling technique for qualitative data and 25 third grade students of SD N 1 Tuko for quantitative data. The instrument used interviews to find out the problems experienced then analyzed by triangulating the data then the questionnaire data was analyzed using descriptive statistics. The results showed that teachers used LKS and picture books as a source of reading fairy tales. Teachers have not innovated digital media integrated with local wisdom so that students are less interested in using the media. From the results of the study it can be concluded that students and classroom teachers need innovative reading sources for children's literature dogeng that can improve literacy quality, namely to understand the content of reading.